THE IMPACT OF ENERGY ON GLOBAL GEOPOLITICS POST COVID-19 - Kunkunrat Kunkunrat (Jurnal Ekonomi, 2021)
Understanding the development of low-carbon energy systems and the end of today's fossil fuel-based systems is critical to predicting the future of global energy geopolitics. As renewable energy is a post-COVID-19 goal, geopolitical tensions between fossil fuel producing countries have been exposed. This research examines the impact of the Covid-19 pandemic on the energy sector and how these changes affect global geopolitical dynamics. This research uses a qualitative approach with descriptive methods. The research results show that the COVID-19 pandemic has been a significant trigger in accelerating the energy transition towards renewable energy sources. The impact involves a shift in global dependence on fossil fuels, with producing countries facing declining influence while countries innovative in renewable technologies gain geopolitical advantage. International collaboration on renewable energy is proving crucial in accelerating global adoption, while decreasing global dependence on fossil fuel supplies is changing geopolitical power dynamics. Increasing energy independence, while bringing opportunities, also raises technical challenges that need to be overcome.